Technology blueprint: HelmAlert by SAFE4U Sdn. Bhd. - Azharun, Nur Fatini Arisyaa; Hanif, Nurhasanah; Mohd Noor Azam, Nurin Irdina; Mohd Yazid, Siti Zaidatul Akma Zaidi (2025)
SAFE4U Sdn. Bhd. brings HelmAlert as an advanced safety sensor helmet that can prevent accidents in high maintenance areas like construction sites, plantation and emergency services. The helmet has vibration alerts, a global positioning system tracker, and the impact detection switch that is driven using the ESP32 microcontroller. Having one-touch activation and 12-hour rechargeable battery, HelmAlert offers real-time warnings about the hazards surrounding us without the necessity of mobile apps and outside connectivity. In this way, its ergonomical design provides comfort to use it during a long period of time, and it is a practical, smart, and cheap PPE solution. HelmAlert will offer active protection to hazards unlike in conventional helmets where individuals only had passive protection. It has no need for smartphones and applications, and it is perfectly suited to the rural and off-grid conditions. HelmAlert is a rare occurrence when a smart device is affordable, high enough in terms of features and is user-friendly and therefore will be adopted in both industrial and agricultural fields in large numbers as compared to either high-end helmets such as those provided by MSA Safety or those of the basic kind such as Proguard. The team is also well-qualified with a chief executive officer who has more than 10 years’ experience in the operation of a business, a marketing manager with a record in brand development, a financial manager with a good accounting background, and a good HR manager. The team is well supported by legal, financial, and creative advisors that allow them to implement the business strategy and introduce HelmAlert to the market successfully.